2006
DOI: 10.1590/s0103-84782006000600048
|View full text |Cite
|
Sign up to set email alerts
|

Anticorpos anti-Neospora caninum em bovinos, ovinos e bubalinos no Estado do Rio Grande do Sul

Abstract: RESUMO A infecção peloO Neospora caninum (N. caninum) é um protozoário coccídio que tem sido considerado a principal causa de abortos em bovinos (ANDERSON et al., 1991). O agente foi descrito e caracterizado inicialmente em cães nos Estados Unidos (DUBEY et al., 1998) e, desde a sua descrição inicial, tem sido diagnosticado em várias espécies, inclusive em bovinos (DUBEY & LINDSAY, 1996). A enfermidade associada à infecção por esse parasita é denominada de neosporose.O ciclo biológico do Neospora caninum foi p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 14 publications
1
5
1
3
Order By: Relevance
“…Higher occurrence of seropositive sheep were observed in this study in the state of Rio Grande do Sul, in strong contrast to the study by Vogel et al (2006), who found a prevalence of only 3.2% in sheep by ELISA. The municipalities with higher occurrences of seropositive sheep (Bagé/Uruguaiana, Sant'Ana do Livramento, São Manuel and Pirajuí) were statistically significant different from the other studided municipalities and from each other when analyzed in pairs (2×2) in the univariate analysis, except São Manuel and Sant'Ana do Livramento.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Higher occurrence of seropositive sheep were observed in this study in the state of Rio Grande do Sul, in strong contrast to the study by Vogel et al (2006), who found a prevalence of only 3.2% in sheep by ELISA. The municipalities with higher occurrences of seropositive sheep (Bagé/Uruguaiana, Sant'Ana do Livramento, São Manuel and Pirajuí) were statistically significant different from the other studided municipalities and from each other when analyzed in pairs (2×2) in the univariate analysis, except São Manuel and Sant'Ana do Livramento.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, factors intrinsic to the technique, such as the specific characteristics of the secondary antibody, alterations in the conditions of antigen-antibody reaction, the diversity of antigen preparations and the degree of subjectivity of the IFAT results, given that the interpretation of serological reactions is performed visually (BJÖRKMAN & UGGLA, 1999). Furthermore, larger numbers of seropositive sheep may be detected in studies using samples from problem herds (VOGEL et al, 2006) and although N. caninum is closely related to Toxoplasma gondii, Sarcocystis spp.,and other apicomplexans, cross-reactivity has not been a major issue in serologic assays (DUBEY & LINDSAY, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Of all 64 sheep studied, three animals (4.69%) tested positive for anti-N. caninum IgG antibodies. Similar results were reported by Špilovská et al (2009) in Slovakia and Vogel et al (2006) in a study performed in Rio Grande do Sul, southern Brazil, where 3.7% (14/382) and 3.2% (2/62) sheep were seropositive, respectively. In Mossoró, Rio Grande do Norte, northeastern Brazil, the positive rate reported by Soares et al (2009) was also low (1.8%; 7/409).…”
Section: Discussionsupporting
confidence: 90%
“…To the authors' knowledge, this is the first study reporting the occurrence of N. caninum infection in female water buffaloes in the State of Pernambuco, Northeastern Brazil. In Brazil, the prevalence of N. caninum infection in water buffaloes varies from 14.6% to 88.0% (FUJII et al, 2001;SOUZA et al, 2001;GENNARI et al, 2005;RODRIGUES et al, 2005;VOGEL et al, 2006;GONDIM et al, 2007;SILVA et al, 2010SILVA et al, , 2014SILVA et al, , 2017GALVÃO et al, 2013;BRASIL et al, 2015;CHRYSSAFIDIS et al, 2015;PORTELLA et al, 2016). Comparing results across seroepidemiogical surveys carried out by different researchers is particularly challenging, as the methodology applied, including sampling and diagnostic tests can vary between studies, especially concerning IFAT cut-off values.…”
Section: Discussionmentioning
confidence: 99%
“…buffalo herd is in Northeast, with 10,437 thousand heads located in the state of Pernambuco (IBGE, 2016). Many serological surveys on N. caninum infection in water buffaloes have been carried out by researchers in different parts of the world with prevalences ranging from 1.50 to 88.30% (BRASIL et al, 2015;CAMPERO et al, 2007;CHRYSSAFIDIS et al, 2015;DUBEY et al, 1998;FUJII et al, 2001;FERROGLIO et al, 2003;GALVÃO et al, 2013;GONDIM et al, 2007;GUARINO et al, 2000;GENNARI et al, 2005;HUONG et al, 1998;HAMIDINEJAT et al, 2015;KONNAI et al, 2008;KONRAD et al, 2013;MEENAKSHI et al, 2007;MOORE et al, 2014;NASIR et al, 2011;NEVERAUSKAS et al, 2015;PORTELLA et al, 2016;RODRIGUES et al, 2005;ROMERO-SALAS et al, 2017;SOUZA et al, 2001;SENGUPTA et al, 2012;SILVA et al, 2010SILVA et al, , 2014SILVA et al, , 2017VOGEL et al, 2006;YU et al, 2007).…”
Section: Introductionmentioning
confidence: 99%